2019
DOI: 10.1016/j.jtos.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model for contact lens wear reveals clandestine IL-1R dependent corneal parainflammation and susceptibility to microbial keratitis upon inoculation with Pseudomonas aeruginosa

Abstract: Purpose Contact lens wear carries a risk of complications, including corneal infection. Solving these complications has been hindered by limitations of existing animal models. Here, we report development of a new murine model of contact lens wear. Methods C57BL/6 mice were fitted with custom-made silicone-hydrogel contact lenses with or without prior inoculation with Pseudomonas aeruginosa (PAO1-GFP). Contralateral eyes served as controls. Corneas were monitored for pathology, and examined ex vivo using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 86 publications
(103 reference statements)
3
48
0
Order By: Relevance
“…However, there is growing evidence that the antimicrobial property of tears and the unique surface of the eye, combined with the nightly vacuuming by neutrophils and help from resident populations of other immune cells such as macrophages, prevent infections (Liyanage et al, 2016;Liu et al, 2017). While the eye has also been reported to have a microbiome (Lu and Liu, 2016), pathogen growth is infrequent unless there is foreign body involvement (i.e., contact lenses) or an injury (i.e., abrasion) that exposes the underlying surface (Metruccio et al, 2019). In addition, when the host is immunosuppressed and neutropenic, following organ transplantation or cancer treatment, for example (Ozkan et al, 2017;Nanda et al, 1991), the eye may rapidly succumb to opportunistic bacteria such as Pseudomonas aeruginosa, a leading cause of bacterial keratitis (Sy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that the antimicrobial property of tears and the unique surface of the eye, combined with the nightly vacuuming by neutrophils and help from resident populations of other immune cells such as macrophages, prevent infections (Liyanage et al, 2016;Liu et al, 2017). While the eye has also been reported to have a microbiome (Lu and Liu, 2016), pathogen growth is infrequent unless there is foreign body involvement (i.e., contact lenses) or an injury (i.e., abrasion) that exposes the underlying surface (Metruccio et al, 2019). In addition, when the host is immunosuppressed and neutropenic, following organ transplantation or cancer treatment, for example (Ozkan et al, 2017;Nanda et al, 1991), the eye may rapidly succumb to opportunistic bacteria such as Pseudomonas aeruginosa, a leading cause of bacterial keratitis (Sy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of standardised methods and paucity of information on animal models means comparing ex vivo studies is difficult, and there is dispute regarding the suitability of different animal models. Ex vivo models used to investigate bacterial keratitis include mice [ 137 , 138 , 139 , 140 , 141 ], rabbits [ 140 , 141 , 142 , 143 , 144 , 145 , 146 ], goats [ 147 ], cows [ 148 ] and pigs [ 149 , 150 , 151 ]. It is currently unknown if interspecies differences in the thickness of the corneal epithelium [ 108 , 152 ] and stroma [ 153 , 154 , 155 ] play a major role in development and progression of infection in the ex vivo cornea.…”
Section: Modelling Biofilm Infectionsmentioning
confidence: 99%
“…In vivo modelling involves the use of live animals. Rat [ 171 ] and rabbit [ 172 , 173 , 174 ] models have been reported, but mouse models currently dominate the literature [ 131 , 137 , 138 , 175 , 176 , 177 , 178 ]. Despite its smaller size, the murine cornea contains more corneal epithelial cell layers than the human cornea and the ratio of epithelial to stromal cells is larger [ 179 ].…”
Section: Modelling Biofilm Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several groups described that epithelial cells at the wound edges of injured airway epithelia exposed to P. aeruginosa bacteria or P. aeruginosa virulence factors feature reduced or loss of lamellipodial structures, stress fibers, focal adhesions and destruction of the actin cytoskeleton (de Bentzmann et al, 2000; Geiser et al, 2001; Losa et al, 2015) (Figure 1B). In a novel murine model of contact lens wear, it has been shown that PAO1 inoculation is associated with altered cell morphology, disrupted basal membrane and disorganized epithelial structure, with or without corneal opacity (Metruccio et al, 2019).…”
Section: Evidence For Epithelial Integrity Alterations By Pseudomonasmentioning
confidence: 99%